Measuring the Effect of Gender-Based Policies on Economic Growth - Agénor, Pierre-Richard; Canuto, Otaviano (World Bank, Washington, DC, 2012)
To this day, policy makers, policy advisers, and economists in development institutions do not have any practical tools to help them to assess the impacts of policies aimed at promoting gender equality and quantify the effect of these policies on growth. Yet, there has been limited effort in that direction. This note lays out such a tool, a framework for quantifying the growth effects of gender-based policies in developing economies, developed recently in the context of a research project sponsored by the World Bank. The framework is based on analysis using a computable overlapping generation's model that accounts for the impact of access to infrastructure on women's time allocation, as well as human capital accumulation and inter- and intergenerational health externalities. The analysis also presents illustrative gender-based experiments in a calibrated version for a low-income country (Benin).